Improved tagmentation-based whole-genome bisulfite sequencing for input DNA from less than 100 mammalian cells. (February 2015) - Lu, Hanlin; Yuan, Zhimei; Tan, Tao; Wang, Junwen; Zhang, Juyong; Luo, Hui-Juan; Xia, Yudong; Ji, Weizhi; Gao, Fei
Aim: To develop a whole-genome methylation sequencing method that fulfills the needs for studies using ultra-low-input DNA.Materials & methods: The tagmentation-based whole-genome bisulfite sequencing (T-WGBS) technology is modified, enabling stable library construction with complexity from minimally 0.5 ng of initial genomic DNA, which equals less than 100 mammalian cells.Results: We thoroughly assessed the performance of this T-WGBS method by sequencing the methylomes of a rice strain and pre-implantation embryos of rhesus monkey and compare to traditional WGBS approach, thereby demonstrating the efficacy of this new approach.Conclusion: This new approach is highly attractive for the complete methylome analysis of very few cells, for example, mammalian pre-implantation embryos, or tiny human biopsy specimens.